Relações intertextuais na obra de Ana Maria: ficção e história, teoria e criação literária - Vieira, Ilma Socorro Gonçalves (2013)
This research deals with dialogical relationships established in some of Ana Maria Machado‟s novels and juvenile books, having as the theoretical background the studies based on Bakhtin‟s principle of dialogism, which was highly important for the development of the concept of intertextuality, coined by Julia Kristeva. Taking into account the scope of the dialogical relationships recreated in the Brazilian writer‟s works, this study aims at investigating “intertextuality” through a more flexible point of view, by focusing on history as an intertext in the writer‟s fictional production and in the metafictional process as a dialogue between theory and literary creation. Regarding the relationships between historical and fictional discourse in Ana Maria Machado‟s works, one understands that the texts related to the colonization of America as well as those which refer to the process of dictatorship in Brazil are absorbed as fixed linguistic structures in the official historical discourse. They are, above all, eminent processes marked by tensions in human relationships, which are full of symbolic meaning. The theoretical basis to deal with the topics formerly mentioned are Hayden White‟, Paul Ricoeur‟, Luiz Costa Lima‟, Erich Auerbach‟, Linda Hutcheon‟, AndreTrouche‟, Maurice Halbachs‟, Gaston Bachelard‟ and Gilbert Durand‟s studies. As far as the metafictional process of the works are concerned, one understands that the dialogue between the theory and literary creation goes beyond the limits of the text in construction and promotes a revolutionary effect in the subject involved by the literary writing, because, while they are writing, Ana Maria Machado‟s characters deal with the process of writing itself, and, at the same time, they are able to recognize and reconstitute themselves. Friedrich Schiller‟s philosophical approach about literary creation, Linda Hutcheon‟s theories about the narcissistic narrative and the postmodern poetry, besides Lucien Dällenbach‟s theories about mise en abyme are the theoretical references used in the investigation of this dialogue.